Efficient charge-transfer from diketopyrrolopyrroles to single-walled carbon nanotubes. Issue 26 (29th June 2021) - Papadopoulos, Ilias; Menon, Arjun; Plass, Fabian; Molina, Desiré; Harreiß, Christina; Kahnt, Axel; Spiecker, Erdmann; Sastre-Santos, Ángela; Guldi, Dirk M.
Abstract : In this contribution, the excited state charge-transfer interactions between single-walled carbon nanotubes (SWCNTs) and a variety of phenyl, 4-bromophenyl, and thiophene substituted diketopyrrolopyrroles (DPPs), is described. Abstract : In this contribution, the excited state charge-transfer interactions between single-walled carbon nanotubes (SWCNTs) and a variety of phenyl, 4-bromophenyl, and thiophene substituted diketopyrrolopyrroles (DPPs), is described. Atomic force microscopy (AFM) and aberration corrected high resolution transmission electron microscopy (AC-HRTEM) corroborated the successful formation of DPP/SWCNTs. Steady-state absorption, fluorescence, and Raman spectroscopies all gave insights into the impact on their ground and excited states as well as on the nature of their electronic communication/interaction. Of great value was time-resolved transient absorption spectroscopy on the femto- and nanosecond time-scales; it assisted in deciphering the charge-transfer mechanism from the DPPs to the SWCNT and in analyzing the dynamics thereof with transfer efficiencies of up to 81%. Important confirmation for the one-electron oxidized DPPs came from pulse radiolysis assays with focus on establishing their spectral fingerprints. Our full-fledged work demonstrates that the successful preparation of stable DPP/SWCNTs represents an important step towards establishing them as a viable alternative to porphyrin-based systems in emerging applications such as solar energy conversion.